أثر الاستعمار في ازدواجية الهوية في الرواية العربية: "شوق الدرويش" لحمور زيادة أنموذج / The influence of Colonialism in the Duality of Identity in Arabic Novel: A Case Study of Ḥammūr Ziyādah’s “Syauq al-Darwīsh” - Al Izzah, Sana Samih (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2017)
ملخص البحث: يهتم هذا البحث برصد التغيرات المتعددة في الهوية القومية، نتيجة التحولات المختلفة التي واجهها الوطن العربي في ظل الاستعمار الغربي، ويركز البحث على محاولة المستعمِر خلخلة الهُوية وطمسها؛ لضمان استمرارية تبعيته السياسة والاقتصادية والثقافية، وتناول البحث نمطاً روائياً يمثل تلك المرحلة بأبعادها المختلفة، لاستخلاص الدلالات التي يحملها النص عبر وسائل تمكنه من الكشف عن مكنونات الثقافة الاستعمارية، والتي ظهرت من خلال البعثات التبشيرية التي فعلت ما عجز الاستعمار عن فعله بالقوة والقمع، وهو تحويل المستعمَر إلى الدين المسيحي بطريقة الترغيب. وجاءت الوسائل المختلفة التي حاول المستعمِر من خلالها بسط نفوذه وهيمنته؛ لتشتيت الهوية وتشظيها من خلال القهر والاستبداد، والظلم والعنف، وبث الشبهات حول الدين الإسلامي وكذلك الشعور بالانقسام والاغتراب الذي أوجده التمييز العنصري في الشعوب المستعمَرة غير البيضاء، ومغريات العولمة؛ لتشويق المستعمَر الأخذ بمظاهر الحضارة الغربية. وخلص البحث إلى أن ازدواجية الهوية جاء عن رغبة المستعَمر في الحفاظ على مصالحه في البلاد، أو الشعور بالدونية والرغبة في التماهي مع الآخر الأقوى أو الانبهار بثقافة الغرب وحضارته. الكلمات المفتاحية: البعثات التبشيرية -القهر - التمييز العنصري- العنف –العولمة. Abstract: The study attempts to trace the various changes in national identity as the result of the developments that ensued from western colonization by focusing on the efforts of the colonialist to disrupt its identity and obliterate it to maintain its cultural, political and economic subjugation over its subjects. The study attempts to tackle this dimension through indicating its manifestation in the genre of novel in order to arrive at the inferences carried by the text. This is done through methods that would enable identification of the elements of the colonial culture. This was manifest in the missionaries which managed to achieve what the military did not by force by attracting the subjects to Christianity by encouraging them to do so. There were various means through which the colonialist dispose its power and might to obliterate the identity of its subjects through force, subjugation, discrimination and violence. This is in addition to instilling confusion in the understanding of Islam and through the feeling of isolation and detachment that accompanied racism in the non-white subjects apart from the temptations of globalization in order to excite the minds to accept the western civilizations. The study concludes that duality in identity is the result of the interest of the colonized people’s interest to preserve their interests in their countries or it is the feeling of nihilism along with the empathy with the stronger ‘other’ or a fascination with the Western culture and its civilization. Keywords: Missionaries- subjugation- racism- violence- globalization. Abstrak: Kajian ini berusaha menjejak pelbagai perubahan identiti kebangsaan sebagai kesan kepada perkembangan yang disebabkan oleh penjajahan dengan tumpuan kepada usaha-usaha pihak penjajah untuk mengubah dan menundukkan identiti kelompok dijajah dengan tujuan mengekalkan dominan budaya, politik dan ekonominya. Kajian ini memperincikan dimensi ini dengan menunjukkan ciri-ciri ini yang tersurat dan tersirat dalam genre novel. Ini dilaksanakan melalui metod yang dapat mengenalpasti unsur-unsur budaya penjajah. Ini dapat diperhatikan daripada gerakan Kristian yang telah dapat mencapai tujuan yang tidak dapat dicapai oleh pihak tentera dengan menarik masyarakat yang dijajah untuk menukar agama. Terdapat beberapa cara yang yang digunakan oleh pihak penjajah untuk mempengaruhi identiti masyarakat dijajah dengan kekerasan, penundukan, diskriminasi dan kekejaman. Ini disamping strategi seperti percubaan mengelirukan dalam memahami Islam dan dengan menyuntik perasaan keterasingan yang ditinggalkan amalam perkauman dalam kalangan bangsa bukan kulit Putih yang dijajah. Keterujaan yang dicetuskan globalisasi turut menjadi alat untuk menarik minda pihak yang dijajah untuk menerima ketamadunan Barat. Kajian ini merumuskan yang isu dualiti identiti adalah kesan daripada keinginan pihak dijajah untuk memelihara maslahat mereka di negara-negara mereka atau ia adalah disebabkan oleh perasaan ketidakupayaan disamping perasaan ingin memahami pihak penjajah yang lebih tinggi kedudukannya ataupun kerana keterujaan disebabkan oleh budaya barat dan ketamadunnya. Kata kunci: Gerakan Kristian- penundukan- perkauman- kekerasan- globalisasi.